Robustness for unidirectional carbon/glass fibre reinforced hybrid epoxy composites under flexural loading - Dong, Jonathan; Kalantari, M.; Davies, I. (Elsevier Ltd, 2015)
A study on the robustness of unidirectional S-2 glass and T700S carbon fibre reinforced epoxy hybrid composites under flexural loading is presented in this paper. The flexural strengths of various stacking configurations are computed using the Classic Lamination Theory (CLT), and the computed data are fitted to a regression model. With the aid of the developed regression model, robust indices are developed for both flexural strength and specific flexural strength. The concept of robust strength is introduced to address both the strength and robustness criteria, with which a design guideline for robust hybrid composites is given. Simulation studies are conducted to demonstrate the validity of the proposed method.